2020
DOI: 10.1097/bpo.0000000000001576
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Comparison of Patient-selected Operative Versus Nonoperative Treatment of Scheuermann Kyphosis

Abstract: Background: Scheuermann kyphosis (SK) can be managed operatively or nonoperatively. Few studies compare the effect of operative versus nonoperative treatment on patient health-related quality of life. We compare 2-year radiographic and the Scoliosis Research Society-22 questionnaire (SRS-22) results of patients who self-selected either conservative or surgical treatment. Methods: Single institution review of prospectively collected data for patients pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Based on the previous research, surgical treatment of SK in the adolescent population results in significant improvements in HRQOL when measured using the SRS-22 outcome score. 12 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the previous research, surgical treatment of SK in the adolescent population results in significant improvements in HRQOL when measured using the SRS-22 outcome score. 12 , 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…At 2 years postoperatively, the HRQOL of SK patients improved to reach equivalent values to the AIS scores. Green et al 15 compared 2-year radiographic and the SRS-22 results of 45 patients who self-selected either conservative or surgical treatment. At 2-year follow-up, surgical patients experienced a significant change on all parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who receive operative treatment for Scheuermann's have been shown to have improvements in radiographic outcomes, less pain, and greater satisfaction compared to nonoperative patients. 15 While controversial, magnetic resonance imaging (MRI) is probably not routinely indicated on all patients as part of the preoperative assessment if pain is at the apex of the curve or in a hyper-lordotic lumbar spine below a hyper-kyphotic thoracic spine. Tight hamstrings, such as a popliteal angle of 60 degrees or less is common, especially in adolescent males and is not by itself a sign of neurologic pathology.…”
Section: Key Conceptsmentioning
confidence: 99%
“…Spinal deformity correction requires a long posterior instrumentation, while spondylolisthesis is treated with a single or two-level lumbar fusion [ 1 ]. Previous studies have suggested that PSF reduces pain in patients with AIS and spondylolisthesis, while pain outcomes after surgery for SK remain unclear [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%